Clicking on Heaven’s Door: The Effect of Immigrant Legalization on Crime - Pinotti, Paolo (American Economic Review, 2017)
We estimate the effect of immigrant legalization on the crime rate of immigrants in Italy by exploiting an ideal regression discontinuity design: fixed quotas of residence permits are available each year, applications must be submitted electronically on specific “click days,” and are processed on a first come, first served basis until the available quotas are exhausted. Matching data on applications with individual-level criminal records, we show that legalization reduces the crime rate of legalized immigrants by 0.6 percentage points on average, on a baseline crime rate of 1.1 percent. (JEL J15, J61, K37, K42)